Release Kinetics Studies of Ibuprofen from Sustained Release Microcapsules - Hossain, M Belal; Rashid, M; Ahmed, M; Shaheen, SM; Motahar, AKM (Dhaka University Journal of Pharmaceutical Sciences, 2007)
Dhaka Univ. J. Pharm. Sci. Vol.4(1) 2005 The full text is of this article is available at the Dhaka Univ. J. Pharm. Sci. website